Activation of the Calcium Receptor by Calcimimetic Agents Is Preserved Despite Modest Attenuating Effects of Hyperphosphatemia. Issue 1 (January 2022) - Goodman, William G.; Ward, Donald T.; Martin, Kevin J.; Drayer, Debra; Moore, Carol; Xu, Jiahong; Lai, James; Chon, Yun; Nemeth, Edward. F.
Significance Statement: Hyperphosphatemia may contribute to secondary hyperparathyroidism among patients with CKD, but the mechanism responsible remains uncertain. Recent in vitro studies indicate that high levels of phosphorus attenuate the level of calcium receptor activation, and this observation has led to speculation that hyperphosphatemia diminishes the efficacy of calcimimetic agents when used clinically. Using data from large, prospective clinical trials of the calcimimetic agents etelcalcetide and cinacalcet, the authors demonstrate that hyperphosphatemia modestly reduces the effect of these agents in lowering parathyroid hormone (PTH) levels among those with secondary hyperparathyroidism undergoing hemodialysis. These findings demonstrate a role for phosphate as a negative modulator of calcium receptor activation in vivo in humans, but overall, it does not modify the PTH-lowering effect of either agent in a therapeutically meaningful way. Visual Abstract: Abstract : Background: Phosphorus levels in the range seen clinically among patients undergoing dialysis have been reported to attenuate calcium receptor activation and modify parathyroid hormone (PTH) release from isolated parathyroid glands in vitro . Some clinicians and providers of dialysis thus have suggested that calcimimetic agents are ineffective and should not be used to manage secondary hyperparathyroidism among those undergoing dialysis when serum phosphorus concentrations exceed certain threshold levels. Methods: To determine whether hyperphosphatemia diminishes the therapeutic response to calcimimetic agents, we used data from large clinical trials to analyze the effects of etelcalcetide and cinacalcet to lower plasma PTH levels in individuals on hemodialysis who had secondary hyperparathyroidism and varying degrees of hyperphosphatemia. Results: Plasma PTH levels declined progressively during 26 weeks of treatment with either etelcalcetide or cinacalcet without regard to the degree of hyperphosphatemia at baseline. However, with each calcimimetic agent, the decreases in PTH from baseline were less at each interval of follow-up during the trials among participants with serum phosphorus levels above one of three prespecified threshold values compared with those with serum phosphorus levels below these thresholds. Conclusions: These in vivo findings are the first in humans to support the idea that hyperphosphatemia attenuates calcium receptor activation by calcium ions and by calcimimetic agents. The effect of hyperphosphatemia on the responsiveness to calcimimetic agents appears relatively modest, however, and unlikely to be significant therapeutically. The efficacy of treatment with calcimimetic agents for lowering plasma PTH levels among those with secondary hyperparathyroidism remains robust despite substantial elevations in serum phosphorus.